Road surface erosion in a Loess Plateau watershed: Roles of road conditions, upslope contributing areas, and hydrological connectivity - Mengmeng Li; Juying Jiao; Qian Xu; Xiqin Yan; Ziqi Zhang; Jun Liao; Zeng Yan; Wenting Zhao; Xiaohan Jiang; Na Deng (CATENA, 2026)

Icaritin improves pregnancy outcomes in endometriosis by inhibiting ovarian granulosa cell senescence - Yalun He; Jie Ding; Yangshuo Li; Ji Sun; Cuiping Wei; Na Sun; Runnan Jiang; Ziming Zhao; Xiaolan Liang; Yiming Chen; Wen Cheng; Litai Zhang; et al. (Molecular Biology Reports, 2026)

Columnar optical properties of locally emitted light-absorbing carbonaceous aerosols - Kang Hu; Hong Liao; Dantong Liu; Jianbing Jin; Siyuan Li; Yangzhou Wu; Yuxing Gao; Xiaotong Jiang; Shitong Zhao; Ping Tian; Fei Wang; Na Kang; et al. (Journal of Environmental Sciences, 2026)

NIR-responsive mesoporous core-shell nanoplatform with oxygen self-supply and cascade targeting for reversing doxorubicin resistance via synergistic chemo-phototherapy - Yufeng Li; Yuping Jiang; Kexuan Wang; Xinyi Liu; Rui Yang; Lu Han; Tao He; Na Li; Da Huo (Chemical Engineering Journal, 2026)

Fe(II)-driven abiotic-biotic relay alleviates denitrification bottleneck via chemical nitrite reduction and intracellular carbon - Na Hu; Qi Feng; Chenxi Li; Yuanyuan Liu; Baoli Zhu; Tianci Guo; Lei Tong; Jianbo Shi; Robert A. Sanford; Shuyi Li; Yu He; Yidan Hu; et al. (Water Research, 2026)

Photodegradation process of microplastics mediated by biochar-derived dissolved organic matter: Insights from density functional theory calculations - Kunliang Jiang; Zaifeng Wang; Huacheng Xu; Zhaoliang Peng; Yuxuan Zhang; Wenkang Li; Shengkai Zhou; Qingru Wan; Na Song (Chemical Engineering Journal, 2026)

Enhanced degradation of sulfamethoxazole in dielectric barrier discharge plasma via Zn tetrahedral site doping-mediated d-band center engineering of CoFe2O4 - Xiaojing Wang; Rui Cao; Na Huang; Mengmeng Du; Mingyao Yuan; Jia Ma; Fan Zhang; Jiaqi Jiang; Zhenxing Zeng; Yanzong Zhang; Zhilin Li; Shihuai Deng (Chemical Engineering Journal, 2026)

Spatiotemporal characteristics of O3 pollution and source apportionment of reactive precursors in Shenyang, China - Na Jiang; Sixiao Guo; Wenyu Fan; Xiaochao Li; Changfeng Liu (Atmospheric Pollution Research, 2026)

Cadmium stress restructures bacterial communities but induces limited variation in predicted functional profiles in the rhizosphere of Sedum plumbizincicola: implications for Cd phytoremediation - Yanan Cheng; Jing Jiang; Shangqi Xu; Meng Na; Xiaoping Li; Jihai Zhou (Rhizosphere, 2026)

AI for membrane bioreactors: Fouling prediction and decision support - Mingchao Zhu; Shuangqian Gao; Yue Chen; Shuping Li; Jiang Meng; Junling Yang; Na Li; Yongze Lu; Guangcan Zhu (Journal of Water Process Engineering, 2026)

Stronger actions are needed to advance PM2.5 mitigation and its health benefits under population aging in China: Evidence from China’s Clean Air Actions - Jian Qian; Ruoyu Li; You Zou; Jiayi Chen; Junyu Wang; Sheng Li; Na Yang; Tianyue Han; Xin Wang; Chenglin Tao; Nan Wang; Menglu Jiang; et al. (Journal of Hazardous Materials, 2026)

Why toxin genes are not enough: regulatory and life-cycle controls shape dinoflagellate toxicity - Yue Jiang; Na Wang; Bernd Krock; Kenneth Mertens; Zhun Li; Hyeon Ho Shin; Nihal G. Shams El-Din; Ophélie David; Iria Garcia Moreiras; Eduardo Pérez-Vega; Kirsty Smith; Haifeng Gu (Harmful Algae, 2026)

TBK1 associates with TRIF and TRAF3 related IRF3, IRF7, and type I IFN signaling in large yellow croaker Larimichthys crocea - Ying Li; Wen Qi Zha; Wen Feng Cui; Meng Jia Li; Yan Mi Na Chen; Qiu Ye Huang; Qiao Yun Yang; Ying Jia Shen; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

The cytokinin oxidase/dehydrogenase MdCKX4 regulates drought tolerance in Malus domestica - Tong Li; Yu-Feng Zhang; Joy Xin-Yue Zhai; Zi-Quan Feng; Shuo Ma; Xin-Yi Li; Huai-Na Gao; Long-Xin Luo; Zhi Li; Qi Zhang; Min-Min Zhou; Ya-Li Zhang; et al. (Plant Science, 2026)

Prediction of solute transport in three-dimensional rough-walled rock fractures: The role of geometrical heterogeneities - Na Huang; Zhenhui Wang; Yujing Jiang; Ju Wang; Bo Li (Journal of Hydrology, 2026)

Identifying driving factors of lacustrine groundwater discharge in Lake Taihu with integrated surface-subsurface numerical modeling - Hao Zhou; Yadong Shi; Yue Zou; Ya Jiang; Na Zheng; Subin Cheng; Donghao Wu; Xin Luo; Chaomeng Dai; Juntao Zheng; Zhi Li (Journal of Hydrology, 2026)

Machine learning Identifies the impacts of the Eastern route of the South-to-North water diversion Project on the transformation of dissolved organic matter - Na Huang; Penghui Li; Yilan Jiang; Lin Chen; Dawei Wang (Journal of Hydrology, 2026)

Socioeconomic drivers of riverine biochemical oxygen demand: Insights from interpretable machine learning - Na Huang; Dawei Wang; Penghui Li; Lin Chen; Wei Wang; Zeng Zhou; Pei Xu; Sile Li; Yali Zhang; Yilan Jiang (Journal of Environmental Management, 2026)

Biotransformation of 2-Aminobenzothiazole by a newly isolated Rhodococcus sp. YQ-4 eliminates its toxicity to sensitive organisms - Fuyu Song; Jiaxi Liu; Qi Wu; Aiqin Diao; Yinhu Jiang; Xin Yan; Na Li; Jian He; Jiguo Qiu (International Biodeterioration & Biodegradation, 2026)

Simultaneous enantioselective determination of 30 chiral pesticides in vegetables: enantiomeric composition, separation, and absolute quantification using LC-MS/MS - Tianyue Zhao; Xin Jiang; Yingjie Zhu; Danning Shen; Chunzheng Li; Danli Liu; Hui Li; Yanqing Cao; Kun He; Na Wang (Food Chemistry, 2026)

Multi-resolution ozone mapping over the Yangtze River Delta (2014–2022) using a data-driven spatial weighting and downscaling framework - Na Yang; Jian Qian; Junyu Wang; Jiayi Chen; Sheng Li; Xin Wang; Chenglin Tao; Nan Wang; Menglu Jiang; Tao Zhang; Fei Yin; Yue Ma (Atmospheric Pollution Research, 2026)

Gas Concentration Prediction Model with the Multi-scale and Multi-factor Based on GMKNet - XingYu Gong; RongKun Jiang; Yu Guan; Yi Yang; Na Li (Natural Resources Research, 2026)

Study on the engineering characterization of stabilized cadmium-contaminated soil using MgO activated FA and GGBS - Cuihong Li; Yubo Zhou; Wei Wang; Shaoyun Pu; Na Li; Ping Jiang (Bulletin of Engineering Geology and the Environment, 2026)

Study on the Effects of Feeding and Starvation on the External Morphology and Gonadal Development of Artificially Matured American Eel - Lan Wang; Jialun Liu; Zhongmei Yang; Tongxi Ai; Feng Zhao; Keji Jiang; Lei Gao; Mingfei Li; Ye Ding; Na Zhao; Wei Jiang; Xinhui Wei; et al. (Fishes, 2026)
The aim of this study is to investigate how external nutrient supply affects the allocation of reproductive energy during artificial ripening of American eels (Anguilla rostrata), as well as the physiological regulatory mechanisms involved in their bodies. Healthy female American eels were selected for the experiment and randomly divided into two groups: feeding group and starvation group (simulating the natural migration of American eels without eating). The initial weight of the feeding group was (308.43 ± 36.99 g), and the initial weight of the starvation group was (291.67 ± 63.31 g). The entire experiment was divided into two stages: the first stage was a 6-month nutritional reinforcement period, during which the feeding group was regularly fed with Vannamei shrimp, while the starvation group was not fed throughout the entire process. The second stage was a 3-month artificial ripening stage, during which both groups of eels stopped feeding. Inject 1 mL of mixed hormone (containing 6.5 mg of carp pituitary extract CPE+200 IU human chorionic gonadotropin HCG per mL per week) into each eel for a total of 12 injections to induce gonadal maturation. Both groups of eels did not die during the experiment, with a survival rate of 100%. As the gonads continue to develop and mature, the growth and development advantages of the feeding group of eels are very obvious: body weight, chest circumference, and gonadal index are significantly higher than those of the starvation group. After completing 12 hormone injections, the gonadal index of the feeding group reached (32.72 ± 7.01%), while that of the starvation group was only (4.35 ± 2.48%). Under artificial ripening conditions, the egg diameter of the feeding-eel group increased rapidly in the later stage of the experiment. The growth rate of eggs in the starvation group was slow, and the final egg diameter was significantly smaller. The diameters of the nuclei of both groups of oocytes increased synchronously with the progress of the experiment; the number of nucleoli in the feeding group first increased and then decreased, while the number of nucleoli in the starvation group continued to increase. The oil droplets inside both sets of eggs gradually increased in size, and the oil droplets fed to the eggs in the middle and late stages of maturation had a larger volume. Hormone test results showed that the testosterone (T) level in the eel fed group increased significantly in the later stage of the experiment. This indicates that adequate nutrition can alleviate the inhibition of the reproductive endocrine axis through positive feedback regulation of the pituitary gonad (BPG) axis. Nutritional reinforcement before ripening can promote gonadal development and enhance reproductive capacity by regulating the distribution of nutrients between muscles and gonads. The results of this study provide a solid theoretical basis for improving the nutritional management plan for parent fish in the fully artificial breeding process of American eels.

Persistent testicular glycogenolysis and active lipid metabolism during torpor in hibernating Siberian chipmunks - Zhe Wang; Lu-Fan Li; Yu-Jing Yan; Ming-Yan Yuan; Xiang-Yu Zhao; Li-Na Jiang; Xian-Feng Yi (Journal of Thermal Biology, 2026)

Screening of proteins interacting with vhvp-2 protein from Vibrio parahaemolyticus causing translucent post-larvae disease in Pacific white shrimp Litopenaeus vannamei - Na An; Li Jiang; Yilin Wang; Zhe Du; Yun Wei; Qifan Zeng; Mengqiang Wang (Journal of Invertebrate Pathology, 2026)

Preparation of negative carbon cement soil by corn straw biochar collaborative carbonization technology: Mechanical properties, carbon sequestration evaluation, microscopic mechanism - Pengfei Wei; Wei Wang; Xukun Ma; Na Li; Chenjun Wang; Yong Liu; Ping Jiang; Miaomiao Sun (Journal of Environmental Management, 2026)

Co-precipitated protein prepared by soybean protein and phycocyanin: Focus on protein structure and nutritional characteristics - Na Sun; Zhe Wang; Jianan Li; Lanxin Li; Shi Liu; Jianling Feng; Ruihan Su; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Chemistry, 2026)

One-step treatment of refractory organic pollutants from landfill leachate: alternating magnetic field synergies persulfate activation and in-situ coagulation - Dawei Wang; Yingying Li; Yilan Jiang; Yihan Zhu; Na Huang; Keyi Gao; Jiarong Li; Shijie You (Chemical Engineering Journal, 2026)

Ultrahigh energy storage density under a low electric field in Sm-modified lead-free high-entropy perovskite ceramics - Chengyou Wang; Jiangnan Hu; Li Wang; Chong Zhao; Na Tu; Xin Nie; Dongxu Li; Chao Chen; Xiaokun Huang; Xiangping Jiang (Chemical Engineering Journal, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

The G143S substitution of cytochrome b confers field resistance to pyraclostrobin in Glomerella cingulata - Xushi Jiang; Qian Yang; Yibo Man; Yichen Ma; Yujie Lu; Na Liu; Caixia Wang; Sen Lian; Baohua Li; Weichao Ren (Pesticide Biochemistry and Physiology, 2026)

Application of rice husk biochar in foam lightweight filler: Investigating sustainable development potential of innovative subgrade materials - Erlu Wu; Pengfei Wei; Na Li; Ping Jiang; Wei Ding; Wei Wang (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Effects of quinoa addition on physicochemical properties, microbiome profiles, and volatile organic compounds in medium-temperature Daqu” [Food Res. Int. 223 (2026) 117868] - Wei Cheng; Chao Jiang; Tianquan Pan; Qingyun Zhu; Gengdian Liu; Na Li; Zaijie Wu; Xingjiang Li (Food Research International, 2026)

Time and pH regulation of the morphology and structure evolution of soybean protein fibrils: Focusing on foaming mechanism and application - Jianan Li; Zhe Wang; Bowen Yang; Xinhui Peng; Shi Liu; Na Sun; Ruihan Su; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2026)

Protective effects of melatonin on mouse ovarian tissue against oxidative stress and ferroptosis may involve the MT1 receptor - Sheng Nan Jiang; Xin Zhang; Li Na Si; Meng Wei; Xin Hui Wei; Yong Wei Wang; Tie Cheng Sun; Song He Yang; Zhi Hong Chen; Lu Yang Cheng (Cryobiology, 2026)

Interpretable deep learning method integrating spatial self-attention for generating bias-corrected high-resolution GFS precipitation forecasts - Haiyang Wang; Shufeng Lai; Chongxun Mo; Tao Feng; Changhao Jiang; Na Li (Atmospheric Research, 2026)

Post-earthquake road accessibility assessment in mountainous counties incorporating geological hazard density correction: A case study of Pingshan County, Hebei Province - Qiu-na Guo; He Zhang; Hong-yu Wang; Fan Yang; Jiang Li; Si-yu Liu (Applied Geophysics, 2026)

Single-cell profiling and machine learning identify cuproptosis-related fibroblast subpopulations and fibrogenesis modulator AEBP1 in endometriosis - Erqing Huang; Jiang-Tian Li; Danhui Zuo; Ruijie Li; Qingyue Wu; Na Lin; Jinru Zhao; Huajing Wang; Yi Liu; Ling Zhang (Apoptosis, 2026)

Engineering TadA8e-based base editors for GhWOX1 editing to create cotton with diverse leaf shapes - Guanying Wang; Shihe Jiang; Meijing Li; Yao He; Mingju Zhu; Fengjiao Hui; Li Yang; Jie Yu; Yongxue Hu; Mengqin Tang; Na Zhang; Bo Li; et al. (Science China Life Sciences, 2026)

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

Flavor characterization of Chenxiang-type baijiu-Daoguang nianwu aged in wooden Jiuhai with different vintages integrating GC-E-nose, GC-IMS, GC-MS-O, ROAV and chemometrics approaches - Na Wang; Xiangyang Zhang; Li Xue; Zhen Zhang; Li Fu; Xuejiao Ren; Hui Zhang; Bo Zhang; Xiaoyu Jiang; Lili Zhang; Mei Wang (Food Research International, 2026)

Spatiotemporal distribution and host association of antibiotic resistance genes in sediment of Qiantang river basin - Qiannan Jin; Jie Li; Yantan Zhou; Guangqian Zhao; Yuhan Jiang; Na Cheng; Lifang Hu (Environmental Geochemistry and Health, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Effects of cadmium-tolerant bacteria combined with biochar on cadmium and selenium dynamics in rice grown on seleniferous soils: Insights from a soil bacterial community analysis - Yanan Cheng; Jing Jiang; Lanping Song; Shangqi Xu; Meng Na; Kun Cheng; Daming Li; Shoubiao Zhou; Jihai Zhou (Journal of Environmental Chemical Engineering, 2026)

Thermal runaway inhibition of the adipic acid synthesis reaction based on organic core phase change microcapsules - Lei Ni; Yuanyuan Li; Qichao Wang; Juncheng Jiang; Zhiquan Chen; Luping Gu; Na Li; Dongxiao Zhang (Journal of Environmental Chemical Engineering, 2026)

Enhanced metal-organic framework-driven deep learning-assisted magnetic crystal paper aptsensor for two-step sensitization and in-situ detection of pathogenic bacteria - Lulu Cao; Yuwei Ren; Shengshi Jiang; Hui Li; Maoling Hu; Xin Zhang; Xiaoyu Yu; Weichao Wu; Mengyu Li; Zhao Liang; Na Ling; Hongzhou Chen; et al. (Chemical Engineering Journal, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

Validation and Correction of In-Orbit Tangent Height for the Ozone Monitoring Suite-Limb onboard FY-3F - Song Liu; Yuan Li; Na Xu; Lin Chen; Peng Zhang; Minzheng Duan; Yapeng Wang; Jiachen Wang; Ruonan Jiang (Journal of Meteorological Research, 2026)

Digital grievances: A geospatial analysis of public discourse on doctor-patient conflict in China - Pu Zhang; Yiliang Li; Zheng Wei; Pan Hui; Na Jiang (Applied Geography, 2026)

Pyocyanin induces rice benzoxazinoid synthesis to co-drive cadmium immobilization in rhizosphere microdomain: Microbial metabolite-mediated spatiotemporal communication mechanisms - Shengwei Yi; Zan Tian; Lanlan Wei; Feng Li; Lizhong Zhu; Fangbai Li; Songxiong Zhong; Fei Ge; Na Liu; Xionghui Ji; Jiang Tian; Yujun Wu (Soil Biology and Biochemistry, 2026)

Effects of nutrient forms on the bloom dynamics and phytoplankton community associated with Prorocentrum cordatum - Chuang Li; Yicheng Wang; Na Jiang; Shuangqing Li; Chenyang Shao; Fengyuan Zhang; Huajun Zhang; Weizhong Chen; Hailong Huang; Haibo Jiang (Harmful Algae, 2026)

Parameter Sensitivity Analysis and Applicability Evaluation of AquaCrop-OSPy Model Based on EFAST Method for Major Grain Crops in Southwest China - Wentao Zhang; Qiliang Yang; Wenqian Zhang; Fuchang Jiang; Ling Yang; Na Li (International Journal of Plant Production, 2026)

Two new abietane diterpenoids from Salvia cavaleriei var. simplicifolia - Qian Wu; Jie Yang; Mi-Na Yang; Li-Jia Ye; Hong-Fen Jiang; Miao Zhang; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2026)

A concept-drift-driven hybrid modeling framework for high-resolution ambient surface NO2 retrieval in Beijing-Tianjin-Hebei Region, China - Junyu Wang; Jian Qian; Jiayi Chen; Caiying Luo; Sheng Li; Na Yang; Ruoyu Li; You Zou; Tao Zhang; Fei Yin; Chenglin Tao; Nan Wang; et al. (Journal of Hazardous Materials, 2026)

Leveraging large language models to explain provincial heterogeneity in online discussion of water pollution in China: A socioeconomic and environmental perspective - Pu Zhang; Na Jiang; Yiliang Li; Zheng Wei; Pan Hui (Journal of Cleaner Production, 2026)

Study on mechanical properties of non-diagenetic hydrates-bearing sediments under in-situ static conditions - Na Wei; Jiang Wu; Haitao Li; Jun Pei; Shouwei Zhou; Jinzhou Zhao; Bjørn Kvamme; Richard Banks Coffin; Anping Feng; Jianyong Feng (Fuel, 2026)

Black phosphorus quantum dots regulate inflammation and neural stem cells differentiation via Notch1 signaling through cell adhesion - Lu Chen; Yongyuan Guo; Lusen Shi; Shiji Zhang; Linlin Jiang; Yong Chang; Haoran Liu; Zihang Wang; Na Li; Shiqing Feng (Chemical Engineering Journal, 2026)

Viscosity-tunable polyvinyl alcohol/tannic acid supramolecular adhesive with ethanol as an intermolecular physical interaction modulator - Ninglu Zhang; Liangxian Liu; Yuyan Jiang; Haiyu Li; Na Wang; Ming Wei; Dexiu Min; Zhenqian Pang; Yanjun Xie; Jian Li; Shaoliang Xiao (Chemical Engineering Journal, 2026)

Pectic polysaccharides from Mongolian medicinal Hypecoum leptocarpum: Structure and ulcerative colitis amelioration via gut microbiota and intestinal inflammation regulation - Cunwuliji Na; Xiang Shi; Jicheng Fu; Jiahao Li; Hongyu Jiang; Zhiwei Guo; Hongyan Lai; Zhipeng Zhang; Longyan Zhao; Qingxia Yuan; Baoshun Zhang (Carbohydrate Polymers, 2026)

Enhancing Blood Fingerprints with Multicolored Conjugated Polymers: A Fluorescent Strategy with Python-Based Quantitative Assessment - Zimin Zhang; Yuhao Zhang; Xuelian Jiang; Na Rao; Mingzhu Wu; Ying Li; Di Peng (Journal of Fluorescence, 2026)

Effects of quinoa addition on physicochemical properties, microbiome profiles, and volatile organic compounds in medium-temperature Daqu - Wei Cheng; Chao Jiang; Tianquan Pan; Qingyun Zhu; Gengdian Liu; Na Li; Zaijie Wu; Xingjiang Li (Food Research International, 2026)

Liquid-derived carbon encapsulated nanoporous SiOx anode for long-cycle lithium-ion batteries - Liewu Li; Chufang Chen; Qianqian Jiang; Zhencheng Huang; Jie Peng; Haoran Wei; Xiaoyu Gong; Na Feng; Shenghua Ye; Xuming Yang; Xiangzhong Ren; Jianhong Liu; et al. (Chemical Engineering Journal, 2026)

The single nucleotide polymorphism rs155787 on the autophagy gene of SQSTM1 is associated with silicosis susceptibility: A multi-stage study - Lijing Jiang; Fan Wang; Mingwei Huai; Wendi Zhang; Xiaofeng Chen; Chunping Li; Xinsheng Zhang; Bingchen Liu; Yao Su; Minjie Chu; Na Sun; Jiandong Jiao; et al. (Toxicology Letters, 2025)

GAS1 affects proliferation, apoptosis, and steroid hormone levels by regulating mitochondrial functions and the PI3K/AKT pathway in bovine granulosa cells - Wenjie Yu; Na Pei; Haitao Jia; Yijing Yin; Hong Xu; Tian Tian; Chang Liu; Lingxia Xu; Ze Li; Zibin Liu; Xiaoshi Cai; Mingkai Yu; et al. (Theriogenology, 2025)

Mechanical properties of monolithic EPS-coated lightweight soil: unconfined compressive strength and small-strain dynamic characterization - Ping Jiang; Xinghan Wu; Wei Wang; Na Li; Haihua Zhan; Guoxiong Mei; Jianfeng Wang (Soil Dynamics and Earthquake Engineering, 2025)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

Engineering V-based Prussian blue analogue cathodes toward ultrahigh capacity and rate capability in aqueous zinc-ion batteries - Yan Chen; Na Shen; Xinyu Guo; Chang Li; Chengcheng Zhu; Nan Jiang; Xi Liu; Wenjun Deng; Rui Li (Chemical Engineering Journal, 2025)

Engineering Escherichia coli nissle 1917 with lactonase ZHD101 alleviates zearalenone-induced intestinal disruption and reproductive toxicity in rat - Min Dai; Siyuan Liu; Renming Cai; Deqiang Li; Yijiao Wen; Jingwen Jiang; Na Hao; Qin Wang; Xiaowei Gao (World Journal of Microbiology and Biotechnology, 2025)

Synergistic electromagnetic and chemical enhancements in Al/C3N4/Ag@C for Raman-based chlortetracycline sensing - Jingyi Sun; Lujie Li; Tingting Zhang; Na Jiang; Zishan Guo; Congying Li; Weihua Li; Xianhuai Huang; Yan Li; Rui Lu (Analytica Chimica Acta, 2025)

Unveiling regulatory network of porcine oocyte IVM using integrated multi-omics - Yufen Jiang; Helin Li; Na Cheng; Yuchen Han; Qiue Xu; Mingjin Li; Muhammad Ameen Jamal; Jianxiong Guo; Honghui Li; Hong-Jiang Wei; Wenmin Cheng (Livestock Science, 2025)

Screening of proteins interacting with infectious hypodermal and hematopoietic necrosis virus in Pacific white shrimp Litopenaeus vannamei - Na An; Li Jiang; Zhe Du; Yilin Wang; Mengqiang Wang (Fish & Shellfish Immunology, 2025)

Screening of proteins interacting with PirA and PirB from Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease in Pacific white shrimp Litopenaeus vannamei - Li Jiang; Na An; Rong Fan; Dianli Zhao; Mengqiang Wang (Fish & Shellfish Immunology, 2025)

Ethylene-responsive factor HvERF72 regulates starch synthesis and B-type starch granules initiation in barley - Gaozong Zhou; Jinjin Ding; Yulong Li; Qiang Xu; Yazhou Zhang; Huaping Tang; Pengfei Qi; Mei Deng; Jian Ma; Guoyue Chen; Jirui Wang; Na Lin; et al. (Carbohydrate Polymers, 2025)

Experimental research on citric acid modified magnesium oxysulfate cement composites under dry-wet cycles: Mechanical properties and microscopic mechanism - Na Li; Yifang Song; Wei Wang; Ping Jiang; Xinyu Yan; Jun Zhang; Guoxiong Mei (Sustainable Chemistry and Pharmacy, 2025)

Microplastics and human health: Exposure pathways, toxicity mechanisms, and future research challenges - Zhi Wang; Nuo Li; Yongcheng Ding; Na Li; Menghan Su; Congcong Zhang; Yiqun Li; Qing Wang; Chenyan Sha; Bing Xia; Jie Cheng; Guan Jiang (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Uncovering key genes of K1 capsule Cronobacter on environmental resilience” [Food Bioscience 67 (2025) 106224] - Zongyang Li; Na Ling; Shengshi Jiang; Xihao Wang; Yingwang Ye (Food Bioscience, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Insights into the multiple nitrogen removal mechanisms of anammox consortia induced by iron scraps - Shuyan Yin; Yi-Xuan Wang; Muyu Li; Na Li; Cheng Hou; Xinbai Jiang; Jinyou Shen (Chemical Engineering Journal, 2025)

Modification effects of regional temperature and humidity on the relationship between daily mortality and short-term coexposure to fine particulate matter and ozone - Jing Zeng; Jian Qian; Jiayi Chen; Sheng Li; Junyu Wang; Menghan Yao; Qianqian Du; Na Yang; Tao Zhang; Fei Yin; Chenglin Tao; Xinyin Xu; et al. (Atmospheric Environment, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

Multi-omics analysis reveals the molecular mechanism of silibinin rescue the toxic effects of butyl benzyl phthalate on porcine preimplantation embryos - Yu Li; Guangjun Huang; Na Li; Zihao Zhang; Hanwen Zhang; Qian Gao; Zhaokang Cui; Yi Jiang; Yilong Miao (Journal of Hazardous Materials, 2025)

Constructing nitrogen-doped porous organic polymer- supported single-atom cobalt catalysts for highly efficient hydroformylation of internal olefins - Yuqing Wang; Miao Jiang; Na Liu; Tian Tian; Changdao Li; Zhao Sun; Gewen Yu; Yanming Wang; Wenxiu He; Jian Ding; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2025)

Deep soil moisture has limited impact on mitigating drought stress effects on plant transpiration in a subtropical secondary forest - Ji Zhang; Na Liu; Cicheng Zhang; Xinping Zhang; Xinguang He; Wulin Jiang; Jiajie Li; Ziwei Zhan; Dejing Peng; Dongjie Lv; Suixia Ni (Plant and Soil, 2025)

The Role of HbA1c in Parkinson's Disease: An Integrative Analysis by Single-Cell, Bulk Transcriptome and Mendelian Randomization - Huihe Zhang; Wei Li; Juwei Wang; Zhimin Wu; Na Zhao; Yue Jiang (Molecular Neurobiology, 2025)

Ni nanoparticles inlaid in amorphous silicon nitride-derived nickel phyllosilicate: A highly stable and active catalyst for ammonia decomposition - Han Yang; Jing Li; Qiang Chang; Qun-chao Zhao; Meng-na Zhang; Huan-jiang Wang; Cheng-hua Zhang; Fei Wang; Xiao-dong Wen (Fuel, 2025)

Acetyl alkannin, a Shikonin monomer, inhibits the ATM/DDR pathway by targeting ATM and sensitizes cisplatin in solid tumors - Xinwen Xu; Jianyi Gu; Peiwen Yang; Lifang Huang; Na Zhao; Jingjing Tang; Zifeng Liang; Qiang Li; Shunqian Wen; Jianwei Jiang; Qing Zhang (Chemico-Biological Interactions, 2025)

CD73 polymorphisms are associated with schizophrenia - He-Xia Peng; Li-Li Zhang; Dan Jiang; Na Jian; Ting-Mei Zhang; Jia-Guo Luo; Hai-Yan Yin (Purinergic Signalling, 2025)
Ecto-5’-nucleotidase/CD73 enzyme plays a key role in the regulation of extracellular adenosine levels, thereby exerting influence on adenosine homeostasis. Emerging evidence suggests that perturbations in purines and ecto-5’-nucleotidase activity are associated with an augmented susceptibility to schizophrenia. However, the precise impact of genetic variations in CD73 on individuals with schizophrenia remains poorly understood. Here, our study demonstrated that rs3734442 allele and rs4431401 heterozygote were conferred a significant risk of schizophrenia disease (rs3734442: odds ratio, 0.556; 95% CI, 0.375 to 0.825; p = 0.004; rs4431401: odds ratio, 1.881, 95% CI, 1.117 to 3.166; p = 0.020). Comparing different genders, we observed a significant association between rs3734442 genotypes and male cases (rs3734442: odds ratio, 0.452; 95% CI, 0.257 to 0.796; p = 0.007). Likewise, there was a significant association between rs4431401 genotypes and male patients (rs4431401: odds ratio, 2.570; 95% CI, 1.196 to 5.522; p = 0.015). Based on family history and antipsychotics medication usage, our data reveals that the rs9444348 allele exhibits the most significant association with familial susceptibility to schizophrenia (odds ratio, 1.541; 95% CI, 1.009 to 2.353; p = 0.048 for A vs G). Moreover, individuals carrying variants of rs6922, rs2229523, and rs2065114 while being treated with clozapine demonstrate a higher frequency proportion compared to those receiving risperidone treatment ( p = 0.035; p = 0.049; p = 0.027 respectively). Additionally, our results indicate that patients with GG genotype of rs9444348 had significantly higher likelihood of using clozapine instead of sulpiride ( p = 0.048). Overall, our data strongly suggest that genetic variations in CD73 are significantly associated with schizophrenia risk and may serve as valuable resources for identifying therapeutic targets.

Electrochemical engineering in aqueous metal-ion batteries - Qi Yang; Na Jiang; Xixian Li; Chunyi Zhi; Jieshan Qiu (Science Bulletin, 2025)

Discovery of isopentenyl flavonoids with inhibitory activity against hepatocellular carcinoma cells based on DeepSAT - Qing Wang; Ben‐Song Xin; Wen-Long Kou; Li-Na Gao; Gu-Xue Zhang; Yan-Jiao Qiao; Guo‐Dong Yao; Xiao‐Xiao Huang; Shao‐Jiang Song (Phytochemistry, 2025)

Maintaining the sustainability of energy-saving behavior: A comprehensive analytical framework based on empirical evidence and game theory - Shuhan Yang; Ruyin Long; Hong Chen; Shiyan Jiang; Jiawei Chen; Jingwen Na; Qian Li (Journal of Environmental Management, 2025)

Composite geopolymer based on copper tailings: Mechanical properties, strength models and microstructure - Wei Wang; Pengfei Wei; Ping Jiang; Na Li; Fuyong Chu; Jiajia Fu; Xudong Wang (Journal of Environmental Chemical Engineering, 2025)

Microbial agents assisted aerobic co-composting of sheep manure and furfural residue: Maturation enhancement and microbial dynamic - Mao Li; Lingwei Jiang; Fei Li; Xuejun Zhang; huanjun Zhao; Na Duan (Journal of Environmental Chemical Engineering, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Prediction of Lithium Mineralization Potential in the Jiulong Area, Western Sichuan (China), Using Spectral Residual Attention Convolutional Neural Network - Haiyang Luo; Na Guo; Chunhao Li; Hang Jiang (Natural Resources Research, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Sensor with Strong Solid Emission for Fluorescence Colormetric Detection of 1, 4-Dioxane in Water and Vapor Based on the Keto-Enol Isomerisation - Jing Wang; Zi-Ao Zong; Shi-Fu Huang; Mohd. Muddassir; Zhi-Yong Xing; Na-Na Li; Wen-Qiong Jiang (Journal of Fluorescence, 2025)

Exploration of energy-saving processes for the separation of tetrahydrofuran/methanol/water: From separation mechanism to experimental validation - Jiahui Zhang; Chao Pan; Chunxiao Ren; Chuanxi Li; Shiying Di; Siqi Jiang; Qizhong Huang; Na Gao; Ningning Wang; Kuo Chang; Lingcong Kong; Zhiyuan Wang; et al. (Fuel, 2025)

Vine tea (Ampelopsis grossedentata) ameliorates chronic alcohol-induced hepatic steatosis, oxidative stress, and inflammation via YTHDF2/PGC-1α/SIRT3 axis - Qihan Luo; Jiang Qiu; Minxia Chen; Na Yang; Xinyue Li; Shuo Huang; Qing Ma; Zongyuan Li; Dayong Lou; Yu Du; Li Chen; Qing Shen; et al. (Food Research International, 2025)

Uncovering key genes of K1 capsule Cronobacter on environmental resilience - Zongyang Li; Na Ling; Shengshi Jiang; Xihao Wang; Yingwang Ye (Food Bioscience, 2025)

Influence of biochar-based microbial agents on post-consumption food waste composting - Qianqi Wang; Sinan Jiang; Na Li; Jiali Lei; Xiaoyan Gong; Guoxue Li; Wenhai Luo (Environmental Research, 2025)

Bonding of wood with high strength and excellent water resistant cellulose colloidal adhesives - Yuyan Jiang; Tian Ju; Liangxian Liu; Haiyu Li; Yue Zhang; Na Wang; Zetan Lu; Ming Wei; Dexiu Min; Yanjun Xie; Jian Li; Yonggui Wang; et al. (Chemical Engineering Journal, 2025)

Optimizing a water-saving and salt-controlling irrigation strategy for improving cotton yield with the AquaCrop model under mulched drip irrigation in saline-alkali soil - Fuchang Jiang; Na Li; Yang Gao; Hongbo Wang; Jiaping Liang; Xingpeng Wang; Jiangtao Du (Irrigation Science, 2025)

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

In-situ constructed ZnAl2O4/A-MoS2 Z-scheme heterojunction for visible-light-thermo cascade catalytic CO2 cycloaddition - Congcong Zhang; Bin Jiang; Runjia Mou; Haochen Shen; Qi Zhou; Longfei Zhang; Jingshuai Li; Na Yang; Luhong Zhang (Journal of Environmental Chemical Engineering, 2025)

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Development of sensitive and rapid immunoassays for Moniliformin (MON) detection based on nanomaterials labeled monoclonal antibodies - Lakshani Madushika; Yongming Huang; Menghan Sun; Yuxuan Liu; Linfang Lu; Xiaoli Li; Na Li; Kang Jiang; Sumei Ling; Shihua Wang (Food Chemistry, 2025)

Involvement of BK Channels and Ryanodine Receptors in Salicylate-induced Tinnitus - Wenying Shi; Qi Zhao; Hongwei Gao; Chao Yang; Zhiyong Tan; Na Li; Feng Jiang; Hongjie Wang; Yonghua Ji; You Zhou (Molecular Neurobiology, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

A framework for the construction of effective landscape ecological network with integrating hydrological connectivity: A case study in Dongjiang River Basin, China - Xin Jiang; Zhi-Yun Jiang; Zhen-Ya Li; Jie Su; Li-Na Tang; Meng-Di Wu; Yi-Jia Wang (Journal of Environmental Management, 2025)

Auxin regulates leaf senescence and nitrogen assimilation to promote grain filling in maize (Zea mays L.) - Na Jiang; Peng Wang; Zhiqi Yang; Changwei Li; Yixiang Xia; Xiangmin Rong; Yongliang Han; Lan Yang (Field Crops Research, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

In vitro antioxidant activity of the polysaccharide from Auricularia auricula and its structural characterisation - Min Lei; Mengqing Wang; Wentao Ma; Na Li; Jiwen Huang; Xinjian Jiang; Wenhui Wu; Chaoyan Zhang (Natural Product Research, 2025)

Regional high iron deposition on brain quantitative susceptibility mapping correlates with cognitive decline in chronic kidney disease patients - Yuan Li; Yuhan Jiang; Bingbing Gao; Na Liu; Yukun Zhang; Huiling Zhou; Qingwei Song; Nan Wang; Yanwei Miao (Brain Imaging and Behavior, 2025)

T-2 toxin triggers immunotoxic effects in goats by inducing ferroptosis and neutrophil extracellular traps - Jing Huang; Kaifeng He; Xin Guo; Jiaxuan Wang; Han Hu; Xuhui Zhang; Na Guo; Yiwen Wang; Wenlong Huang; Rongsheng Huang; Tingting Liu; Xi Jiang; et al. (Toxicology and Applied Pharmacology, 2025)

KCNJ15 inhibits chemical-induced lung carcinogenesis and progression through GNB1 mediated Hippo pathway - Hong-qiang Chen; Na Wang; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Ya-wen Li; Shuang-wu Deng; Zi-yuan Zhou; Wen-bin Liu (Toxicology, 2025)

Green preparation of low-molecular-weight galactomannan from Gleditsia sinensis and mechanistic investigation on ameliorating nonalcoholic fatty liver disease - Chi Feng; Xichuang Cheng; Mula Na; Fenglun Zhang; Jiufang Duan; Li Ji; Jianxin Jiang (Food Research International, 2025)

Carbon dots based cascading nanozymes mitigate phytotoxicity in lettuces under imidacloprid stress - Fengqiong Chen; Ziyan Zhou; Na Yang; Qin Jiang; Xuejie Zhang; Haoran Zhang; Yinjian Zheng; Wei Li; Bingfu Lei (Food Chemistry, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Microbial coadaptation drives the dynamic stability of microecology in mainstream and sidestream anammox systems under exposure of progesterone - Dong-Qi Huang; Jia-Hui Yang; Na-Na Han; Jun-Hui Yang; Yuan Jiang; Zi-Yue Li; Ren-Cun Jin; Nian-Si Fan (Water Research, 2025)

The deformation characteristics of modified lightweight expanded polystyrene soils under cyclical loading - Ping Jiang; Yuming Fu; Wei Wang; Xuhui Zhou; Na Li; Huaqiang Tao (Soil Dynamics and Earthquake Engineering, 2025)

Establishment of highly sensitive lateral flow immunochromatographic strips for quinclorac detection utilizing signal amplification nanoparticles - Yongming Huang; Yuxuan Liu; Menghan Sun; Linfang Lu; Xiaoli Li; Kang Jiang; Na Li; Sumei Ling; Shihua Wang (Food Chemistry, 2025)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Experimental study on oil removal performance and anodic dissolution characteristics during the treatment of marine oil spills using electrocoagulation - Boyan Shao; Yang Liu; Wenming Jiang; Na Chen; Jiaqi Wang; Juanjuan Li (Journal of Water Process Engineering, 2024)

Intimate microbe-water-mineral interactions mediate alkalization in the pyroxene-rich iron ore mines in Panxi area, Southwest China - Yu He; Yongzhe Li; Yue Pan; Jianying Shang; Weimin Sun; Meng Wang; Hao Fan; Robert A. Sanford; Na Wei; Shuming Peng; Daihong Xie; Weiguang Zhang; et al. (Journal of Hazardous Materials, 2024)

High-resolution full-coverage ozone (O3) estimates using a data-driven spatial random forest model in Beijing-Tianjin-Hebei region, China - Junyu Wang; Jian Qian; Jiayi Chen; Sheng Li; Menghan Yao; Qianqian Du; Na Yang; Tao Zhang; Fei Yin; Ying Deng; Jing Zeng; Chenglin Tao; et al. (Journal of Hazardous Materials, 2024)

Study on the strength characteristics and microscopic mechanism of sewage sludge ash modified lime soil - Wei Wang; Pengfei Wei; Na Li; Erlu Wu; Ping Jiang; Junjie Wang (Journal of Environmental Chemical Engineering, 2024)

Fabrication of magnetic Cu2O nanocomposites for enhanced iodide removal: Adsorption properties, mechanism and application - Na Jiang; Juan Bao; Tingting Zhang; Lujie Li; Lan Zhang; Weihua Li; Xianhuai Huang; Jiansheng Li; Rui Lu (Chemical Engineering Journal, 2024)

Hydroxyl radicals dominated the reduction of antibiotic resistance genes by inactivating Gram-negative bacteria during soil electrokinetic treatment - Binxu Li; Kaiyang Jiang; Tingting Song; Mengmeng Yan; Na Li; Zhenzhen Yang; Changxiong Zhu; Hongna Li (Journal of Environmental Management, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Brain Immune Cell Infiltration and Serum Metabolomic Characteristics Reveal that Lauric Acid Promotes Immune Cell Infiltration in Brain and Streptococcus suis Meningitis in Mice - Xuan Jiang; Fengyang Li; Jikun Mei; Tong Wu; Junhui Zhu; Ziheng Li; Zengshuai Wu; Hexiang Jiang; Na Li; Liancheng Lei (Molecular Neurobiology, 2024)

κ-Carrageenan improves the gelation capacity of Antarctic krill myofibrillar proteins through covalent and noncovalent interactions - Shuang Li; Songyi Lin; Pengfei Jiang; Xixin Qian; Shuo Wang; Na Sun (Food Hydrocolloids, 2024)

FTO mediates bisphenol F-induced blood-testis barrier impairment through regulating ferroptosis via YTHDF1/TfRc and YTHDF2/SLC7A11 signal axis - Yu Shi; Li Yin; Jiang-ying Li; Shi-meng Zhou; Na Wang; Hong-qiang Chen; Yong Zeng; Ya-wen Li; Wen-bin Liu (Environmental Pollution, 2024)

Removal performance of Nitrogen, sulfur and chlorine pollutants during chemical looping combustion of textile dyeing sludge using red mud as an oxygen carrier - Hongming Jiang; Yan Lin; Na Gao; Shiwen Fang; Duo Li; Zhen Huang; Hongyu Huang (Chemical Engineering Journal, 2024)

Magnesium hexacyanoferrate nanocatalysts alleviates fibromyalgia syndrome by reversing cellular ferroptosis - Ling Jiang; Zhongqiang Zhu; Kun Han; Dongxu Chen; Lu Huang; Na Hu; Jiayi Du; Bowen Zhang; Yi Su; Tao Li; Xiangyi Ren; Xiang He (Chemical Engineering Journal, 2024)

The association between short-term ozone exposure and fasting blood glucose levels in non-diabetic adults was more obvious in rural residents: the evidence from a typical “urban–rural dual structure” province in southwestern China - Xue-Jiao Li; Ling Li; Li Zhao; Ding-Yan Hu; Na-Na Ma; Hua Xiao; Da-Wei Li; Jie Zhou; Yi-Ying Wang; Ji Zhang; Tao Liu; Yue-Xu Jiang; et al. (Air Quality, Atmosphere & Health, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

A preliminary exploration of waste red-bed as a supplementary cementitious material - Ke Zhang; Haoyang Zeng; Na Li; Feifei Qi; Yiyuan Tan; Laifeng Jiang; Kai Zhang (Journal of Cleaner Production, 2024)

The development of an emotion lexicon for spicy food flavor experience - Lina Ren; Risu Na; Siyi Jiang; Darong Chen; Li Zhang; Hongjun Li; Pengfei Han (International Journal of Gastronomy and Food Science, 2024)

Enhanced immobilization of cadmium and lead in contaminated soil using calcium alginate-modified HAP biochar: Improvements in soil health and microbial diversity - Yining Ji; Na Zheng; Qirui An; Sujing Wang; Siyu Sun; Xiaoqian Li; Changcheng Chen; Shuhai Sun; Yifu Jiang (Environmental Pollution, 2024)

Electrospinning fabrication of hollow C@TiO2/Fe3C nanofibers composites for excellent wave absorption at a low filling content - Bai Jiang; Jianxun Shang; Faying Zhang; Na Li; Yan Wang; Zuming Hu; Junrong Yu (Chemical Engineering Journal, 2024)

Review of reactor systems for hydrogen production via ammonia decomposition - Na Li; Cheng Zhang; Dong Li; Wenbin Jiang; Fojin Zhou (Chemical Engineering Journal, 2024)

Safety and environmental protection application of high performance solid waste unburned ceramsite and its lightweight high strength concrete - Kai-jing Tang; Hong-na An; Chuan-bei Liu; Ying-ding Li; Lu-jun Jia; Yun Tang; Qi-qiang Wang; Yong Jiang; Zi-jian Song (Sustainable Chemistry and Pharmacy, 2024)

Bio-inspired gradient poly(lactic acid) nanofibers for active capturing of PM0.3 and real-time respiratory monitoring - Guiying Zhu; Cunmin Wang; Ting Yang; Na Gao; Yifan Zhang; Jintuo Zhu; Xinjian He; Jiang Shao; Shihang Li; Mingming Zhang; Shenghui Zhang; Jiefeng Gao; et al. (Journal of Hazardous Materials, 2024)

Dynamic variation in the aroma characteristics of Rhus chinensis honey at different stages after capping - Hongxia Li; Yaning Lang; Zhaolong Liu; Mei Song; Ao Jiang; Na Li; Lanzhen Chen (Food Chemistry, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

Regional uncertainty analysis between crop phenology model structures and optimal parameters - Chenyao Yang; Na Lei; Christoph Menz; Andrej Ceglar; Jairo Arturo Torres-Matallana; Siqi Li; Yanling Jiang; Xianming Tan; Lei Tao; Fang He; Shigui Li; Bing Liu; et al. (Agricultural and Forest Meteorology, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Sustained release of a novel bilayer packaging film loaded with binary microemulsion of melatonin/pummelo essential oil and its regulation of postharvest energy metabolism in Agaricus bisporus - Lei Feng; Na Zhang; Jia Wang; Xin Jiang; Jiali Han; Ling Li; Hiroaki Kitazawa; Xiangyou Wang; Cunkun Chen; Yanyin Guo (Food Control, 2024)

An alkali-extracted neutral heteropolysaccharide from Phellinus nigricans used as an immunopotentiator in immunosuppressed mice by activating macrophages - Feihe Wang; Na Li; Hong Li; Yao Di; Fan Li; Peng Jiang; Guiyun Wang (Carbohydrate Polymers, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

New insights into algal-bacterial sludge granulation based on the tightly-bound extracellular polymeric substances regulation in response to N-Methylpyrrolidone - Xiaoyu Zhang; Dan Chen; Na Jiang; Xinying Hou; Yan Li; Yixuan Wang; Jinyou Shen (Water Research, 2024)

GC/MS-based untargeted metabolomics reveals the differential metabolites for discriminating vintage of Chenxiang-type baijiu - Na Wang; Lili Zhang; Li Fu; Mei Wang; Hui Zhang; Xiaoyu Jiang; Xiaohui Liu; Zhen Zhang; Xuejiao Ren (Food Research International, 2024)

Delineating cathodic extracellular electron transfer pathways in microbial electrosynthesis: Modulation of polarized potential and Pt@C addition - Yue Wang; Siyang Yu; Xue Zheng; Xiaobing Wu; Ying Pu; Gaoying Wu; Na Chu; Xiaohong He; Daping Li; Raymond Jianxiong Zeng; Yong Jiang (Bioresource Technology, 2024)

Advancement of foodomics techniques for honey botanical origins authentication: Past decade (2013–2023) and future perspectives - Na Li; Mei Song; Hongxia Li; Zhaolong Liu; Ao Jiang; Yaning Lang; Lanzhen Chen (Trends in Food Science & Technology, 2024)

High efficiency removal of NO using waste calcium carbide slag by facile KOH modification - Fang Wang; Hui Li; Jiyun Gao; Na Geng; Enzhu Jiang; Futing Xia; Mingwu Xiang; Lijuan Jia; Ping Ning (Journal of Environmental Sciences, 2024)

Simulation of inhibition and targeted adsorption of rubberized asphalt VOCs by UiO-66 based on molecular dynamics - Yang Lv; Shaopeng Wu; Haiqin Xu; Na Li; Quantao Liu; Huan Wang; Yingxue Zou; Qi Jiang; Serji Amirkhanian (Journal of Cleaner Production, 2024)

Effect of beta-cypermethrin on the reproductive capacity of female mice in advanced age - Qian-Feng Qiao; Li-Qing Wang; De-E. Yu; Na Li; Qiong-Jun Xu; Yong-Jiang Zhou (Environmental Toxicology and Pharmacology, 2024)

Study on small strain characteristics and microscopic mechanism of rice husk ash modified lime soil - Na Li; Shimeng Yu; Erlu Wu; Xinjiang Song; Ping Jiang; Haibo Xu; Wei Wang (Transportation Geotechnics, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Always positive covalent organic nanosheet enabling pH-independent adsorption and removal of Cr(Ⅵ) - Dong-Xiao Cao; Yun-Jie Zhou; Hong-Xin Jiang; Xue-Nan Feng; Xiao-Yang Liu; Wei Li; Jing-Qi Liu; An-Na Tang; De-Ming Kong (Journal of Hazardous Materials, 2024)

Heat and mass transfer of a novel CO2 desorption process integrated with highly turbulent catalytic heat exchanger - Congning Yang; Tianci Li; Teerawat Sema; Puttipong Tantikhajorngosol; Jingwei Jiang; Xue Bai; Na Jia; Min Xiao; Christine Chan; Paitoon Tontiwachwuthikul (Fuel, 2024)

Utilization of self-assembled soy protein nanoparticles as carriers for natural pigments: Examining non-interaction mechanisms and stability - Shi Liu; Na Sun; Kunyu Ren; Xubin Tan; Lanxin Li; Zhe Wang; Shicheng Dai; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2024)

Pharmacokinetic interactions between tacrolimus and Wuzhi capsule in liver transplant recipients: Genetic polymorphisms affect the drug interaction - Siqi Huang; Wei Song; Shuangmiao Jiang; Yuanchen Li; Min Wang; Na Yang; Huaijun Zhu (Chemico-Biological Interactions, 2024)

Knockdown of SIK3 in the CA1 Region can Reduce Seizure Susceptibility in Mice by Inhibiting Decreases in GABAAR α1 Expression - Zhen-Fu Jiang; Li-Na Xuan; Xiao-Wan Sun; Shao-Bo Liu; Jian Yin (Molecular Neurobiology, 2024)

Polystyrene nanoplastics exposure alters muscle amino acid composition and nutritional quality of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Estimating line contaminant sources in non-Gaussian groundwater conductivity fields using deep learning-based framework - Na Zheng; Zhi Li; Xuemin Xia; Simin Gu; Xianwen Li; Simin Jiang (Journal of Hydrology, 2024)

Degradation of n-hexane by the high-throughput double dielectric barrier discharge: Influencing factors, degradation mechanism and pathways - Ke Li; Ning Jiang; Xiuwen Zhang; Kai Chen; Na Liu; Anton Nikiforov; Jun Chen; Zhiping Ye (Journal of Environmental Chemical Engineering, 2024)

Auxin synthesis promotes N metabolism and optimizes root structure enhancing N acquirement in maize (Zea mays L.) - Na Jiang; Tong Zou; Haitao Huang; Changwei Li; Yixiang Xia; Lan Yang (Planta, 2024)

The source of rock moisture in a sandstone cave in arid northern China: rainfall infiltration or vapor condensation? - Xiao-Wei Jiang; Kai-Gao Ouyang; Xu-Lin Tang; Shu-Cong Tan; Jia-Xin Shi; Na Li; Hong-Bin Yan; Jian-Guang Ren; Li Wan (Hydrogeology Journal, 2024)

Performance and mechanism of graphene oxide removal from aqueous solutions by calcite: adsorption isotherms, thermodynamics, and kinetics - Na Li; Yingdi Pang; Wei Wang; Xinyu Yan; Ping Jiang; Shimeng Yu (Environmental Science and Pollution Research, 2024)

O-acetyl-homoserine sulfhydrylase deficient Streptococcus suis serotype 2 strain SC19 becomes an avirulent strain and provides immune protection against homotype infection in mice - Tong Wu; Hexiang Jiang; Fengyang Li; Xuan Jiang; Jun Wang; Shaopeng Wei; Yi Sun; Yanyan Tian; Hong Chu; Yu Shi; Nan Zhang; Na Li; et al. (Veterinary Microbiology, 2024)

Composting of post-consumption food waste enhanced by bioaugmentation with microbial consortium - Qianqi Wang; Na Li; Sinan Jiang; Guoxue Li; Jing Yuan; Yanming Li; Ruixue Chang; Xiaoyan Gong (Science of The Total Environment, 2024)

Polystyrene nanoplastics induce lipid metabolism disorder and alter fatty acid composition in the hepatopancreas of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Monolithic melamine foam@COF composite: Preparation, characterization and applications in ultrafast removal and on-site quick assessment of Cd2+ pollution - Wei Li; Yue-Lei Hao; Wei-Liang Jin; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Journal of Cleaner Production, 2024)

A comparison of numerical schemes for the GPU-accelerated simulation of variably-saturated groundwater flow - Zhi Li; Daniel Caviedes-Voullième; Ilhan Özgen-Xian; Simin Jiang; Na Zheng (Environmental Modelling & Software, 2024)

Upconversion-based intelligent dual-mode hydrogel nanosensor for visual quantitative detection of formaldehyde - Jiawei Zhu; Na Yu; Cuiqin Bao; Huafeng Shi; Qiang Li; Kai Dai; Changlong Jiang (Chemical Engineering Journal, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Solution plasma synthesis of Pt-decorated Bi12O17Cl2 photocatalysts for efficient upcycling of plastics - Feiyan Wu; Changming Li; Yibo Dou; Jianchi Zhou; Tao Jiang; Yuechao Yao; Na Yeon Lee; Sung Yul Lim; Claus Hélix-Nielsen; Wenjing Zhang (Science of The Total Environment, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

A stable and efficient quasi-solid-state photo/betavoltaic-powered electrochemical cell based on 3-dimensional CdS/ZnO heterostructure - Zan Ding; Renrong Zheng; Wendi Zhao; Tongxin Jiang; Xue Li; Haisheng San; Xin Li; Lifeng Zhang; Na Wang (Chemical Engineering Journal, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Development and Evaluation of Real-Time Polymerase Chain Reaction (PCR) to Authenticate Sablefish ( Anoplopoma fimbria ) in Commercial Seafood Products - Meng Qu; Yanhua Jiang; Yingying Guo; Wenjia Zhu; Shufang Liu; Na Li; Fengling Li; Lin Yao; Zhijun Tan; Lianzhu Wang (Journal of Aquatic Food Product Technology, 2023)

Comparative assessment of food safety regulations and standards for arsenic, cadmium, lead, mercury and iodine in macroalgae used as food and feed in China and Europe - Yingying Guo; Anne-Katrine Lundebye; Na Li; Åshild Ergon; Shaojun Pang; Yanhua Jiang; Wenjia Zhu; Yanfang Zhao; Xiaodong Li; Lin Yao; Lianzhu Wang; Inger Aakre (Trends in Food Science & Technology, 2023)

Cumulative deformation and non-coaxial characteristics of fiber and cement-modified iron tailings under the rotation of principal stress - Ping Jiang; Zhichao Wang; Na Li; Xinjiang Song; Yewen Chen; Wei Wang (Transportation Geotechnics, 2023)

Prevalence of paratuberculosis in cattle in China: A systematic review and meta-analysis - Na Lu; Ya-Ling Niu; Yang Song; Dan-Dan Zhang; Jing Jiang; Jiaqi Wei; Hong-Li Geng; Hongwei Cao (Preventive Veterinary Medicine, 2023)

How much carbon dioxide has the Chinese PV manufacturing industry emitted? - Na Zhang; Yutian Jiang; Xiaojun Zhao; Jiawei Deng; Qianyu Mi; Jie Li (Journal of Cleaner Production, 2023)

ID3 regulates progesterone synthesis in bovine cumulus cells through modulation of mitochondrial function - Zi-Bin Liu; Jia-Bao Zhang; Sheng-Peng Li; Wen-Jie Yu; Na Pei; Hai-Tao Jia; Ze Li; Wen-Fa Lv; Jun Wang; Nam-Hyung Kim; Bao Yuan; Hao Jiang (Theriogenology, 2023)

Nitrification-denitrification co-metabolism in an algal-bacterial aggregates system for simultaneous pyridine and nitrogen removal - Xiaoyu Zhang; Dan Chen; Xinying Hou; Na Jiang; Yan Li; Shijian Ge; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2023)

Carboxyl-containing components delineation via feature-based molecular networking: A key to processing conditions of fermented soybean - Yuye Gao; Yu Fu; Na Li; Yuetong Jiang; Xiaojing Liu; Congcong Gao; Lishuang Wang; Jian-Lin Wu; Tingting Zhou (Food Chemistry, 2023)

The coupling effects between acid-catalyzed hydrothermal pretreatment and acidic/alkaline deep eutectic solvent extraction for wheat straw fractionation - Na Pan; Baiheng Jiang; Jinguang Hu; Mei Huang; Jinsong He; Qin Jiang; Li Zhao; Fei Shen; Dong Tian (Bioresource Technology, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Oral administration of the herbal oligonucleotide XKC-sRNA-h3 prevents angiotensin II-induced hypertension in mice - Kegong Tang; Xiaona Wang; Yu Zhao; Xiaobei Li; Zhenyu Jiang; Song Mei; Mingrui Chen; Yiming Ma; Xinyi Du; Xiangyu Qiao; Na Sun; Jiaqi Liu; et al. (Science China Life Sciences, 2023)

Polystyrene nanoplastics decrease nutrient accumulation, disturb sex hormones, and inhibit reproductive development in juvenile Macrobrachium nipponense - Yiming Li; Yucong Ye; Na Rihan; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2023)

Co-immobilization of β-xylosidase and endoxylanase on zirconium based metal–organic frameworks for improving xylosidase activity at high temperature and in acetone - Na Li; Huan Xia; Yanbin Jiang; Jun Xiong; Wenyong Lou (Bioresource Technology, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

Dynamically adjustable wet ridge for directional liquid movement and controllable coating distribution - Qiuya Zhang; Na Zhang; Ke Li; Yan Li; Xiaofang Zhang; Yi Du; Dongliang Tian; Lei Jiang (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Laboratory characterization of soft clay mixed with EPS, lime, fly ash, and sodium silicate - Ping Jiang; Wenqian Zheng; Lin Zhou; Na Li; Wei Wang (Bulletin of Engineering Geology and the Environment, 2023)

High prevalence of vitamin D deficiency in Asia: A systematic review and meta-analysis - Zhiwei Jiang; Rui Pu; Na Li; Chaozhen Chen; Jialu Li; Wei Dai; Yuchen Wang; Jinxing Hu; Danji Zhu; Qiong Yu; Yuan Shi; Guoli Yang (Critical Reviews in Food Science and Nutrition, 2023)

Identification of contaminant source and hydraulic conductivity field based on an ILUES-SOM surrogate model - Na Zheng; Jinbing Liu; Xuemin Xia; Simin Gu; Yanhao Wu; Xianwen Li; Simin Jiang (Stochastic Environmental Research and Risk Assessment, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Role and Mechanism of BMP4 in Regenerative Medicine and Tissue Engineering - Yiqi Pan; Zhiwei Jiang; Yuer Ye; Danji Zhu; Na Li; Guoli Yang; Ying Wang (Annals of Biomedical Engineering, 2023)

Interactions between white and black carbon in water: A case study of concurrent aging of microplastics and biochar - Shi Yao; Ni Ni; Xiaona Li; Na Wang; Yongrong Bian; Xin Jiang; Yang Song; Nanthi S. Bolan; Qiaozhi Zhang; Daniel C.W. Tsang (Water Research, 2023)

Soil salinity simulation based on electromagnetic induction and deep learning - Simin Gu; Simin Jiang; Xianwen Li; Na Zheng; Xuemin Xia (Soil and Tillage Research, 2023)

Ent-kauranes and ent-atisanes from Euphorbia wallichii and their anti-inflammatory activity - Yali Wang; Qinghua Jiang; Dejuan Sun; Na Zhang; Yu Lin; Hua Li; Lixia Chen (Phytochemistry, 2023)

Efficient estimation of groundwater contaminant source and hydraulic conductivity by an ILUES framework combining GAN and CNN - Na Zheng; Simin Jiang; Xuemin Xia; Weiming Kong; Zhi Li; Simin Gu; Zijun Wu (Journal of Hydrology, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

A new attempt to develop fermented milk with low whey protein allergenic potential using a top-down method - Ruiyang Ma; Na Miao; Qingyi Zhang; Shujuan Jiang; Xinling Li; Lei Chi; Yue Li; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2023)

Livestock grazing-exclusion under global warming scenario decreases phosphorus mineralization by changing soil food web structure in a Tibetan alpine meadow - Feng Sun; Ruiying Chang; Akash Tariq; Jordi Sardans; Josep Penuelas; Hui Jiang; Xingmei Zhou; Na Li (Science of The Total Environment, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Comparison of developmental toxicity of benzophenone-3 and its metabolite benzophenone-8 in zebrafish - Yonghua Wang; Shengnan Jiang; Xi Chen; Xiaodan Liu; Na Li; Yang Nie; Guanghua Lu (Aquatic Toxicology, 2023)

Genome-wide association analysis of resistance to frogeye leaf spot China race 7 in soybean based on high-throughput sequencing - Chen Na; Huanran Miao; Haipeng Jiang; Jinglin Ma; Hongliang Liu; Suchen Lv; Jinghang Zhou; Yuming Yang; Yuhang Zhan; Weili Teng; Yonguang Li; Xue Zhao; et al. (Theoretical and Applied Genetics, 2023)

TRFM-LS: Transformer-Based Deep Learning Method for Vessel Trajectory Prediction - Dapeng Jiang; Guoyou Shi; Na Li; Lin Ma; Weifeng Li; Jiahui Shi (Journal of Marine Science and Engineering, 2023)
In the context of the rapid development of deep learning theory, predicting future motion states based on time series sequence data of ship trajectories can significantly improve the safety of the traffic environment. Considering the spatiotemporal correlation of AIS data, a trajectory time window panning and smoothing filtering method is proposed for the abnormal values existing in the trajectory data. The application of this method can effectively deal with the jump values and outliers in the trajectory data, make the trajectory smooth and continuous, and ensure the temporal order and integrity of the trajectory data. In this paper, for the features of spatiotemporal data of trajectories, the LSTM structure is integrated on the basis of the deep learning Transformer algorithm framework, abbreviated as TRFM-LS. The LSTM module can learn the temporal features of spatiotemporal data in the process of computing the target sequence, while the self-attention mechanism in Transformer can solve the drawback of applying LSTM to capture the sequence information weakly at a distance. The advantage of complementarity of the fusion model in the training process of trajectory sequences with respect to the long-range dependence of temporal and spatial features is realized. Finally, in the comparative analysis section of the error metrics, by comparing with current state-of-the-art methods, the algorithm in this paper is shown to have higher accuracy in predicting time series trajectory data. The research in this paper provides an early warning information reference for autonomous navigation and autonomous collision avoidance of ships in practice.

Euphorfinoids A and B, a pair of ent -atisane diterpenoid epimers from the roots of Euphorbia fischeriana, and their bioactivities - Jiang-Chun Wei; Yu-Ning Gao; Hui-Hui Huang; Xiao-Yu Zhang; Xuan-Li Liu; Xiao-Xu Gao; Na Li; Yue Zhao; An-Hua Wang; Jing-Ming Jia (Natural Product Research, 2023)

Impacts of El Niño–Southern Oscillation on tropical precipitation via triggering anomaly water vapour transport from ocean to land - Jialin Wang; Feifei Pan; Haiyan Li; Pingli An; Guolin Han; Kang Jiang; Xiao Chen; Ziyuan Zhang; Yu Song; Na Huang; Shangqian Ma; Zhenzhen Zhang; et al. (International Journal of Climatology, 2023)
Atmospheric water vapour transport is one of the most active components of the hydrological cycle, which shows great effects on the regional climate variability, while it is largely affected by the large‐scale circulation systems. El Niño–Southern Oscillation (ENSO) shows a remarkable influence on the atmospheric water circulation via disrupting the normal/regular water vapour transport processes, producing the anomaly water vapour fluxes input from ocean to land ( Q net ), and leading to regional precipitation anomalies. However, their quantitative impact has not been fully studied. This study quantified the effect of ENSO on the water vapour transport from ocean to land and identified its impact on tropical precipitation anomalies. The results showed that the global detrended Q net displayed a significantly negative correlation with the strength of ENSO. The notable impact of ENSO on Q net was largely affected by the different patterns of the atmospheric moisture circulation during El Niño and La Niña and was responsible for the change of the spatial distribution of precipitation over the Tropics. El Niño reduced precipitation over the Malay Archipelago and increased precipitation over south China, especially in boreal winter, while La Niña enhanced precipitation over the Malay Archipelago. This study identified the impacts of ENSO on the circulation and water vapour transport process and improved our understanding of the influencing mechanism of ENSO on regional precipitation anomalies, which has important significance on regional water resource management and disaster risk assessment, especially as the extreme climate events have become increasingly frequent.

Systematic characterization of sediment microbial community structure and function associated with anaerobic microbial degradation of PBDEs in coastal wetland - Xu Wang; Guoguang Wang; Chuanyuan Li; Yu Liu; Na Jiang; Xu Dong; Haixia Wang (Marine Pollution Bulletin, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Disruption of the lung-gut-brain axis is responsible for cortex damage induced by pulmonary exposure to zinc oxide nanoparticles - Lingbing Zhang; Yandan Zhang; Xuejun Jiang; Lejiao Mao; Yinyin Xia; Yinzhen Fan; Na Li; Ziqi Jiang; Xia Qin; Yu Jiang; Gang Liu; Feng Qiu; et al. (Toxicology, 2023)

Association between maternal short-term exposure to ambient air pollution and the risk of fetal distress: A matched case-control study - Hua Xiao; Chunyan Yao; Zongli Qi; Jianghong Liu; Xiaoling Liu; Yumeng Zhou; Enjie Tang; Yuegu Hu; Yuexu Jiang; Dawei Li; Ning Du; Na Li; et al. (Science of The Total Environment, 2023)

Metagenomics analysis reveals potential pathways and drivers of piglet gut phage-mediated transfer of ARGs - Yalu Ji; Hengyu Xi; Zhen Zhao; Qiujie Jiang; Chong Chen; Xinwu Wang; Fengyang Li; Na Li; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; et al. (Science of The Total Environment, 2023)

Retraction Note: Downregulation of long non-coding RNA TUG1 suppresses tumor growth by promoting ubiquitination of MET in diffuse large B-cell lymphoma - Hai Cheng; Zhiling Yan; Xue Wang; Jiang Cao; Wei Chen; Kunming Qi; Dian Zhou; Jieyun Xia; Na Qi; Zhenyu Li; Kailin Xu (Molecular and Cellular Biochemistry, 2023)

IL-17A promotes endothelial cell senescence by up-regulating the expression of FTO through activating JNK signal pathway - Na Li; Runan Luo; Wenlong Zhang; Yu Wu; Chaojie Hu; Manli Liu; Diya Jiang; Ziran Jiang; Xinxin Zhao; Yiping Wang; Qing Li (Biogerontology, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Early identification of strawberry leaves disease utilizing hyperspectral imaging combing with spectral features, multiple vegetation indices and textural features - Gangshan Wu; Yinlong Fang; Qiyou Jiang; Ming Cui; Na Li; Yunmeng Ou; Zhihua Diao; Baohua Zhang (Computers and Electronics in Agriculture, 2023)

The aggregation of natural inorganic colloids in aqueous environment: A review - Yihui Guo; Ning Tang; Jiayin Guo; Lan Lu; Na Li; Tingting Hu; Ziqian Zhu; Xiang Gao; Xiaodong Li; Longbo Jiang; Jie Liang (Chemosphere, 2023)

Diterpenoids with anti-inflammatory activity from Euphorbia wallichii - Yali Wang; Dejuan Sun; Qinghua Jiang; Liangliang Xiong; Na Zhang; Yingni Pan; Hua Li; Lixia Chen (Phytochemistry, 2023)

External-loop split-type dynamic membrane photobioreactor for the treatment of high-strength pyridine wastewater: Improved photosynthetic oxygenation and mitigated membrane fouling - Xiaoyu Zhang; Na Jiang; Xinying Hou; Yan Li; Shijian Ge; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Multifunctional hydrophilic MXene/Gelatin composite aerogel with vertically aligned channels for efficient sustainable solar water evaporation and Oil/Water separation - Na Xue; Hongzhi Cui; Weichao Dong; Wenlong Chu; Menghan Li; Heqing Jiang; Na Wei (Chemical Engineering Journal, 2023)

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Visualizing Seizure Propagation in Freely-moving Mice via Miniature Two-photon Microscopy - Zhuoran Zhang; Shihe Jiang; Kaibin Shi; Yan Li; Wei-Na Jin; Qiang Liu; Ting Zhao; Heping Cheng; Fu-Dong Shi (Neuroscience Bulletin, 2022)

Binding characteristics of Pb and Zn to low-temperature feces-based biochar-derived DOM revealed by EEM-PARAFAC combined with general and moving-window two-dimensional correlation analyses - Changjun He; Xuwen He; Run Yuan; Na Li; Jinyuan Jiang (Environmental Science and Pollution Research, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Associations of residential greenness with obesity and BMI level among Chinese rural population: findings from the Henan Rural Cohort Study - Jie Jiang; Zixi Xiang; Feifei Liu; Na Li; Shuyuan Mao; Bo Xie; Hao Xiang (Environmental Science and Pollution Research, 2022)

Refined-JinQi-JiangTang tablet ameliorates hypertension through activation of FGF21/FGFR1 axis in fructose-fed rats - Siming Li; Xiaoling Li; Jing Fan; Xinhang Jia; Hemeng Wang; Fangxin Dong; Haoyang Mao; Chen Zhang; Wenfei Wang; Ye Jiang; Lijun Yan; Na Zhang (Journal of Natural Medicines, 2022)

p-Nitrophenol contaminated soil remediation in a spray-type coaxial cylindrical dielectric barrier discharge plasma system - Nan Jiang; Ying Qu; Zheng Yu; Bangfa Peng; Jie Li; Kefeng Shang; Na Lu; Yan Wu (Environmental Science and Pollution Research, 2022)

The Impact of Economic Development of the Guangdong-Hongkong-Macao Greater Bay Area on Air Pollution: Investigation Based on Remote Sensing Data of Nighttime Lights and Air Pollution - Xiaole Ji; Shaoxing Li; Na Jiang; Fei Wang; Liya Fan; Xiao Niu (Frontiers in Marine Science, 2022)
Whether the Guangdong-Hongkong-Macao Greater Bay Area (GBA) can achieve the goal of environmental protection at the same time as its rapid economic development is an important issue that deserves attention. In this paper, we obtained remote sensing data on air pollution including CO, NO 2 , SO 2 , PM 10 , PM 2.5 , and nighttime light data. We combined the remote sensing data with county-level economic statistics to study economic development and air pollution in the Guangdong-Hongkong-Macao GBA. Our research showed that the economic development in the Guangdong-Hongkong-Macao GBA significantly increased the emissions of NO 2 , PM 10 , and PM 2.5 and did not have significant effects on CO and SO 2 . We constructed an emission intensity indicator of pollutants per unit of luminance. We found that the unit emission intensity of four categories of pollutants, PM 10 , PM 2.5 , SO 2 , and CO, showed a significant decreasing trend in line with economic development. The emission intensity of NO 2 showed a trend of first decreasing and then increasing. The conclusion of this research illustrates that the emission intensity of pollutants per unit of luminosity in the Guangdong-Hongkong-Macao GBA is continuously reducing. The emission of pollutants will gradually change from slow growth to zero growth. However, the emission of NO 2 pollution should be an area of focus in achieving the dual goals of economic development and environmental protection.

Adsorption Characteristics of Modified Eucalyptus Sawdust for Cadmium and Arsenic and Its Potential for Soil Remediation - Jingmin Yang; Xinran Liang; Na Jiang; Zhihong Huang; Fengli Mou; Yanqun Zu; Yuan Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Activation of Autophagy Ameliorates Age-Related Neurogenesis Decline and Neurodysfunction in Adult Mice - Na Yang; Xueqin Liu; Xiaojie Niu; Xiaoqiang Wang; Rong Jiang; Na Yuan; Jianrong Wang; Chengwu Zhang; Kah-Leong Lim; Li Lu (Stem Cell Reviews and Reports, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Decreased incidence of acute hemorrhagic conjunctivitis associated with enhanced public health intervention during the COVID-19 epidemic in China, 2020 - Li Zhang; Xiangyu Guo; Hui Jiang; Na Zhao; Wei Cheng; Wangli Xu; Shelan Liu (Archives of Virology, 2022)

Performance and mechanisms of fly ash for graphene oxide removal from aqueous solution - Ping Jiang; Lin Zhou; Wei Wang; Na Li; Fang Zhang (Environmental Science and Pollution Research, 2022)

MdKCS2 increased plant drought resistance by regulating wax biosynthesis - Xin-Yu Lian; Huai-Na Gao; Han Jiang; Chang Liu; Yuan-Yuan Li (Plant Cell Reports, 2021)

Analysis of the starch properties in tetraploid wheat–Aegilops sharonensis amphidiploid - Qing Li; Xuteng Zhang; Na Lin; Guzmán Carlos; Jingyu Lan; Huaping Tang; Pengfei Qi; Jian Ma; Jirui Wang; Guoyue Chen; Wei Li; Zhien Pu; et al. (Cereal Research Communications, 2021)

Triaxial mechanical properties and micro mechanism of fiber-modified cement soil - Yang Yao; Na Li; Haibo Kang; Wenjie Yu; Chen Zhang; Ping Jiang; Wei Wang (Arabian Journal of Geosciences, 2021)

Component changes of mulberry leaf tea processed with honey and its application to in vitro and in vivo models of diabetes - Huixin Bai; Wei Jiang; Xufang Wang; Na Hu; Linna Liu; Xi Li; Yanhua Xie; Siwang Wang (Food Additives & Contaminants: Part A, 2021)

Associations of residential greenness with hypertension and blood pressure in a Chinese rural population: a cross-sectional study - Jie Jiang; Gongbo Chen; Baojing Li; Na Li; Feifei Liu; Yuanan Lu; Yuming Guo; Shanshan Li; Lifeng Chen; Hao Xiang (Environmental Science and Pollution Research, 2021)

Molecular Cloning and Characterization of FAD6 Gene from Chia (Salvia hispanica L.) - Yufei Xue; Lejing Li; Xuemei Liu; Huanhuan Jiang; Yanping Zhao; Songzhen Wei; Na Lin; Yourong Chai (Biochemical Genetics, 2021)

Associations of acute exposure to airborne pollutants with COVID-19 infection: evidence from China - Bingqing Lu; Na Wu; Jiakui Jiang; Xiang Li (Environmental Science and Pollution Research, 2021)

Extraction and detection of guanosine 5′-diphosphate-3′-diphosphate in amino acid starvation cells of Clavibacter michiganensis - Kaihong Bai; Xing Chen; Na Jiang; Qingyang Lyu; Jianqiang Li; Laixin Luo (Brazilian Journal of Microbiology, 2021)

miR-455-5p regulates atrial fibrillation by targeting suppressor of cytokines signaling 3 - Weiling Li; Na Qi; Shuo Wang; Wenyan Jiang; Tao Liu (Journal of Physiology and Biochemistry, 2021)

Molecular cloning and characterization of two plastidial Δ12 fatty acid desaturase cDNAs from Perilla frutescens - Yufei Xue; Huanhuan Jiang; Baojun Chen; Jiayi Jiang; Na Lin; Lejing Li; Xuemei Liu; Yourong Chai (Acta Physiologiae Plantarum, 2021)

Chronic Neuroinflammation Induced by Lipopolysaccharide Injection into the Third Ventricle Induces Behavioral Changes - Shufang Na; Xuejiao Duan; Rongyan Wang; Yanjie Fan; Ke Xue; Shuwei Tian; Zheqiong Yang; Ke Li; Jiang Yue (Journal of Molecular Neuroscience, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Biomonitoring of heavy metal contamination with roadside trees from metropolitan area of Hefei, China - Ting Fang; Ting Jiang; Kun Yang; Jing Li; Yangyang Liang; Xiuxia Zhao; Na Gao; Hui Li; Wenxuan Lu; Kai Cui (Environmental Monitoring and Assessment, 2021)

Overexpression of a Monodehydroascorbate Reductase Gene from Sugar Beet M14 Increased Salt Stress Tolerance - Jinna Li; Hongli Li; Na Yang; Shuai Jiang; Chunquan Ma; Haiying Li (Sugar Tech, 2021)

SUMOylation of Pdia3 exacerbates proinsulin misfolding and ER stress in pancreatic beta cells - Na Li; Xi Luo; Qilin Yu; Ping Yang; Zhishui Chen; Xinqiang Wang; Jipin Jiang; Jing Xu; Quan Gong; Decio L. Eizirik; Zhiguang Zhou; Jiajun Zhao; et al. (Journal of Molecular Medicine, 2020)

GC usage of SARS-CoV-2 genes might adapt to the environment of human lung expressed genes - Yue Li; Xinai Yang; Na Wang; Haiyan Wang; Bin Yin; Xiaoping Yang; Wenqing Jiang (Molecular Genetics and Genomics, 2020)

Correction to: CCR2 and CCR5 promote diclofenac-induced hepatotoxicity in mice - Zhanke He; Guoquan Wei; Na Li; Mengwei Niu; Shenhai Gong; Guangyan Wu; Teng Wang; Yong Jiang; Peng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Ambient temperature alters body size and gut microbiota of Xenopus tropicalis - Jiaying Li; Junpeng Rui; Yulong Li; Na Tang; Songping Zhan; Jianping Jiang; Xiangzhen Li (Science China Life Sciences, 2020)

Silicon application improved the yield and nutritional quality while reduced cadmium concentration in rice - Na Li; Aixuan Feng; Na Liu; Zhenmao Jiang; Shiqiang Wei (Environmental Science and Pollution Research, 2020)

Analysis of Myoglobin Stability and Bacterial Community Diversity in Mutton Chop Rolls During Cold Preservation - Xue-Qi Zhang; Tao Jiang; Na Guo; Li Bai; Dong-Mei Zhao (Current Microbiology, 2020)

A solvent-assisted active loading technology to prepare gambogic acid and all-trans retinoic acid co-encapsulated liposomes for synergistic anticancer therapy - Kexin Na; Kai Liu; Jiang Yu; Xue Wang; Meng Li; Chutong Tian; Haixia He; Yuan He; Yongjun Wang (Drug Delivery and Translational Research, 2020)

Experimental and Numerical Studies of the Hydraulic Properties of Three-Dimensional Fracture Networks with Spatially Distributed Apertures - Na Huang; Yujing Jiang; Richeng Liu; Bo Li (Rock Mechanics and Rock Engineering, 2019)

RETRACTED ARTICLE: Downregulation of long non-coding RNA TUG1 suppresses tumor growth by promoting ubiquitination of MET in diffuse large B-cell lymphoma - Hai Cheng; Zhiling Yan; Xue Wang; Jiang Cao; Wei Chen; Kunming Qi; Dian Zhou; Jieyun Xia; Na Qi; Zhenyu Li; Kailin Xu (Molecular and Cellular Biochemistry, 2019)

Effects of total dissolved gas supersaturated water at varying suspended sediment concentrations on the survival of rock carp Procypris rabaudi - Cuixia Feng; Na Li; Yuanming Wang; Xiaoqing Liu; Xiaotao Shi; Chenghua Fu; Zhu Jiang; Yao Yang; Haoran Shi (Fisheries Science, 2019)

Effects of dietary protein level on growth performance, digestive enzyme activity, and gene expressions of the TOR signaling pathway in fingerling Pelteobagrus fulvidraco - Qin Qin; Xiu-Fei Cao; Yong-jun Dai; Li-Na Wang; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2019)

Increased CXCL13 and CXCR5 in Anterior Cingulate Cortex Contributes to Neuropathic Pain-Related Conditioned Place Aversion - Xiao-Bo Wu; Li-Na He; Bao-Chun Jiang; Xue Wang; Ying Lu; Yong-Jing Gao (Neuroscience Bulletin, 2019)

Methane emissions responding to Azolla inoculation combined with midseason aeration and N fertilization in a double-rice cropping system - Ya-Dong Yang; He-Shui Xu; Deng-Yun Li; Jing-Na Liu; Jiang-Wen Nie; Zhao-Hai Zeng (Environmental Science and Pollution Research, 2019)

CCR2 and CCR5 promote diclofenac-induced hepatotoxicity in mice - Zhanke He; Guoquan Wei; Na Li; Mengwei Niu; Shenhai Gong; Guangyan Wu; Teng Wang; Yong Jiang; Peng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Synergistic degradation of trans-ferulic acid in aqueous solution by dielectric barrier discharge plasma combined with ozone - Jingyu Ren; Nan Jiang; Jie Li; Kefeng Shang; Na Lu; Yan Wu (Environmental Science and Pollution Research, 2018)

Functional analysis of amino acids at stalk/head interface of human parainfluenza virus type 3 hemagglutinin-neuraminidase protein in the membrane fusion process - Jingjing Jiang; Hongling Wen; Miaomiao Chi; Ying Liu; Jingxue Liu; Zhankui Cao; Li Zhao; Yanyan Song; Na Liu; Lianli Chi; Zhiyu Wang (Virus Genes, 2018)

A new pair of enantiomeric lignans from the fruits of Morinda citrifolia and their absolute configuration - Wen-Jian Liu; Yue-Juan Chen; Dan-Na Chen; Ya-Ping Wu; Yu-Jie Gao; Jing Li; Wen-Jun Zhong; Lin Jiang (Natural Product Research, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Stability of β-carotene microcapsules with Maillard reaction products derived from whey protein isolate and galactose as coating materials - Zhan-mei Jiang; Li-na Bai; Nan Yang; Zhi-biao Feng; Bo Tian (Journal of Zhejiang University-SCIENCE B, 2017)

A novel Enterovirus 96 circulating in China causes hand, foot, and mouth disease - Yi Xu; Yisuo Sun; Jinmin Ma; Shuru Zhou; Wei Fang; Jiawei Ye; Limei Tan; Jingkai Ji; Dan Luo; Liqiang Li; Jiandong Li; Chunxiao Fang; et al. (Virus Genes, 2017)

Effects of Excess Copper Ions on Decidualization of Human Endometrial Stromal Cells - Ying Li; Zhen-Long Kang; Na Qiao; Lian-Mei Hu; Yong-Jiang Ma; Xiao-Huan Liang; Ji-Long Liu; Zeng-Ming Yang (Biological Trace Element Research, 2017)

Post Plasma-Catalysis of Low Concentration VOC Over Alumina-Supported Silver Catalysts in a Surface/Packed-Bed Hybrid Discharge Reactor - Nan Jiang; Cheng Qiu; Lianjie Guo; Kefeng Shang; Na Lu; Jie Li; Yan Wu (Water, Air, & Soil Pollution, 2017)

Activation of group I metabotropic glutamate receptors regulates the excitability of rat retinal ganglion cells by suppressing Kir and I h - Qian Li; Peng Cui; Yanying Miao; Feng Gao; Xue-Yan Li; Wen-Jing Qian; Shu-Xia Jiang; Na Wu; Xing-Huai Sun; Zhongfeng Wang (Brain Structure and Function, 2017)

RNA-Seq Analysis of the Antioxidant Status and Immune Response of Portunus trituberculatus Following Aerial Exposure - Yuquan Li; Shoumin Lai; Renjie Wang; Yuchao Zhao; Hao Qin; Lingxu Jiang; Na Li; Qiang Fu; Chao Li (Marine Biotechnology, 2017)

Review: Mathematical expressions for estimating equivalent permeability of rock fracture networks - Richeng Liu; Bo Li; Yujing Jiang; Na Huang (Hydrogeology Journal, 2016)

A novel diarylheptanoid-bearing sesquiterpene moiety from the rhizomes of Alpinia officinarum - Na Wei; Zhonglin Zhou; Qing Wei; Yong Wang; Jun Jiang; Junqing Zhang; Lixiang Wu; Shuiping Dai; Youbin Li (Natural Product Research, 2016)

First report of human salivirus/klassevirus in respiratory specimens of a child with fatal adenovirus infection - Na Pei; Jiaosheng Zhang; Jinmin Ma; Liqiang Li; Meng Li; Jiandong Li; Yisuo Sun; Jingkai Ji; Hui Jiang; Yong Hou; Fengping Xu; Haorong Lu; et al. (Virus Genes, 2016)

Relationship between molecular weight, monosaccharide composition and immunobiologic activity of Astragalus polysaccharides - Yiping Jiang; Xiaohui Qi; Kai Gao; Wenjun Liu; Na Li; Ningbo Cheng; Gang Ding; Wenzhe Huang; Zhenzhong Wang; Wei Xiao (Glycoconjugate Journal, 2016)

Complement receptor activity of recombinant porcine CR1-like protein expressed in a eukaryotic system - Wei Yin; Xiaoming Wei; Junbing Jiang; Kuohai Fan; Junxing Zhao; Na Sun; Zhiwei Wang; Yaogui Sun; Haili Ma; Xin Zhao; Hongquan Li (Immunologic Research, 2016)

Dust aerosol properties and radiative forcing observed in spring during 2001–2014 over urban Beijing, China - Xingna Yu; Rui Lü; K. Raghavendra Kumar; Jia Ma; Qiuju Zhang; Yilun Jiang; Na Kang; Suying Yang; Jing Wang; Mei Li (Environmental Science and Pollution Research, 2016)

Exploring the correlations between antibiotics and antibiotic resistance genes in the wastewater treatment plants of hospitals in Xinjiang, China - Chao Li; Jianjiang Lu; Jiang Liu; Genlin Zhang; Yanbing Tong; Na Ma (Environmental Science and Pollution Research, 2016)

Dock3 Participate in Epileptogenesis Through rac1 Pathway in Animal Models - Jie Li; Xiujuan Mi; Ling Chen; Guohui Jiang; Na Wang; Yujiao Zhang; Wanni Deng; Zhihua Wang; Guojun Chen; Xuefeng Wang (Molecular Neurobiology, 2016)

The influence of plant root system architectural properties upon the stability of loess hillslopes, Northeast Qinghai, China - Jiang-tao Fu; Xia-song Hu; Gary Brierley; Na Qiao; Qin-qin Yu; Hai-jing Lu; Guo-rong Li; Hai-li Zhu (Journal of Mountain Science, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Combination of PPT with LiCl Treatment Prevented Bilateral Ovariectomy-Induced Hippocampal-Dependent Cognition Deficit in Rats - Na Qu; Xiang-Yu Zhou; Li Han; Lei Wang; Jia-Xin Xu; Teng Zhang; Jiang Chu; Qiao Chen; Jian-Zhi Wang; Qi Zhang; Qing Tian (Molecular Neurobiology, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Effects of heat stress on serum Cortisol, alkaline phosphatase activity and heat shock protein 40 and 90β mRNA expression in rainbow trout Oncorhynchus mykiss - Zhen Li; Zhe Liu; Yan Ni Wang; Yu Jun Kang; Jian Fu Wang; Hai Na Shi; Jin Qiang Huang; Li Jiang (Biologia, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

cDNA cloning, expression, and immunolocalization of gonad-inhibiting hormone (GIH) in Litopenaeus vannamei - Guang-li Li; Si-ping Deng; Shu-na Jiang; Man Ye; Hua-pu Chen; Siuming F. Chan; Chun-hua Zhu (Genes & Genomics, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Development of a test strip for rapid detection of lactoperoxidase in raw milk - Hong-xia Che; Bo Tian; Li-na Bai; Li-ming Cheng; Li-li Liu; Xiao-na Zhang; Zhan-mei Jiang; Xiao-xi Xu (Journal of Zhejiang University-SCIENCE B, 2015)

Protein prenylation and human diseases: a balance of protein farnesylation and geranylgeranylation - Na Xu; Ning Shen; XiuXing Wang; Shan Jiang; Bin Xue; ChaoJun Li (Science China Life Sciences, 2015)

Study on the Diversity of Bacteroides and Clostridium in Patients with Primary Gout - Shi-Chao Xing; Dong-Mei Meng; Ying Chen; Gang Jiang; Xi-Shuang Liu; Na Li; Yao-Yao Yan; Chang-Gui Li (Cell Biochemistry and Biophysics, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Chinese herbal medicine formula Tao Hong Si Wu decoction protects against cerebral ischemia–reperfusion injury via PI3K/Akt and the Nrf2 signaling pathway - Li Li; Na Yang; Ling Nin; Zhilong Zhao; Lu Chen; Jie Yu; Zhuyun Jiang; Zhendong Zhong; Daiwen Zeng; Hongyi Qi; Xiaoyu Xu (Journal of Natural Medicines, 2015)

Promoter hypermethylation may be an important mechanism of the transcriptional inactivation of ARRDC3, GATA5, and ELP3 in invasive ductal breast carcinoma - Da Wang; Peng-Na Yang; Jin Chen; Xian-Yao Zhou; Qiu-Jun Liu; Hong-Jiang Li; Chang-Long Li (Molecular and Cellular Biochemistry, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Breast Cancer Resistance Protein-Mediated Efflux of Luteolin Glucuronides in HeLa Cells Overexpressing UDP-Glucuronosyltransferase 1A9 - Lan Tang; Ye Li; Wei-Ying Chen; Shan Zeng; Ling-Na Dong; Xiao-Juan Peng; Wen Jiang; Ming Hu; Zhong-Qiu Liu (Pharmaceutical Research, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Consistency of the Key Genotypes of Orientia tsutsugamushi in Scrub Typhus Patients, Rodents, and Chiggers from a New Endemic Focus of Northern China - Yun-Xi Liu; Na Jia; Yu-Bin Xing; Ji-Jiang Suo; Ming-Mei Du; Ning Jia; Yan Gao; Li-Jun Xie; Bo-Wei Liu; Shi-Wang Ren (Cell Biochemistry and Biophysics, 2013)

Elevated Plasma Levels of Hypermethylated RASSF1A Gene Sequences in Pregnant Women with Intrahepatic Cholestasis - Ping Yi; Na Yin; Yingru Zheng; Hongmei Jiang; Xinmei Yu; Yaohua Yan; Qiang Liu; Fenglian Xiao; Li Li (Cell Biochemistry and Biophysics, 2013)

An integrative bioinformatics pipeline for the genomewide identification of novel porcine microRNA genes - WEI FANG; NA ZHOU; DENGYUN LI; ZHIGANG CHEN; PENGFEI JIANG; DELI ZHANG (Journal of Genetics, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

Activation of Akt and cardioprotection against reperfusion injury are maximal with only five minutes of sevoflurane postconditioning in isolated rat hearts - Yuan-yuan Yao; Man-hua Zhu; Feng-jiang Zhang; Chuan-yun Wen; Lei-lei Ma; Wen-na Wang; Can-can Wang; Xian-bao Liu; Li-na Yu; Ling-bo Qian; Jian-an Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2013)

Partial or complete substitution of fish meal with soybean meal and cottonseed meal in Chinese mitten crab Eriocheir sinensis diets - Hai-Bo Jiang; Li-Qiao Chen; Jian-Guang Qin; Lu-Jiao Gao; Er-Chao Li; Na Yu; Sheng-Ming Sun; Xue-Qin Jiang (Aquaculture International, 2013)

NBS1 rs1805794G>C polymorphism is associated with decreased risk of acute myeloid leukemia in a Chinese population - Na Li; Yanzhe Xu; Jian Zheng; Lan Jiang; Yonghe You; Hongchun Wu; Wei Li; Depei Wu; Yifeng Zhou (Molecular Biology Reports, 2013)

Functional polymorphisms in PIN1 promoter and esophageal carcinoma susceptibility in Chinese population - Yonghe You; Jieqiong Deng; Jian Zheng; Lan Jiang; Na Li; Hongchun Wu; Wei Li; Jiachun Lu; Yifeng Zhou; Bin Ni (Molecular Biology Reports, 2013)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

The mechanism of mimecan transcription induced by glucocorticoid in pituitary corticotroph cells - Xiao Na Zhang; Li Qiong Xue; He Jiang; Shao Ying Yang; Huai Dong Song; Qin Yun Ma (Molecular and Cellular Biochemistry, 2012)

Enhanced Gene Transduction into Skeletal Muscle of Mice In Vivo with Pluronic Block Copolymers and Ultrasound Exposure - Yun-Chao Chen; Li-Ping Jiang; Na-Xiang Liu; Lu Ding; Xiao-Ling Liu; Zhi-Hui Wang; Kai Hong; Qing-Ping Zhang (Cell Biochemistry and Biophysics, 2011)

Flavonoid Production Is Effectively Regulated by RNAi Interference of Two Flavone Synthase Genes from Glycine max - Yi Na Jiang; Biao Wang; Hui Li; Lu Ming Yao; Tian Long Wu (Journal of Plant Biology, 2010)

Sevoflurane postconditioning reduces myocardial reperfusion injury in rat isolated hearts via activation of PI3K/Akt signaling and modulation of Bcl-2 family proteins - Li-na Yu; Jing Yu; Feng-jiang Zhang; Mei-juan Yang; Ting-ting Ding; Jun-kuan Wang; Wei He; Tao Fang; Gang Chen; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Identification of p27/KIP1 expression level as a candidate biomarker of response to rapalogs therapy in human cancer - Guang Chen; Na Yang; Xiang Wang; Si-Yuan Zheng; Yi Chen; Lin-Jiang Tong; Yi-Xue Li; Ling-Hua Meng; Jian Ding (Journal of Molecular Medicine, 2010)

Structural basis for the decrease in the outward potassium channel current induced by lanthanum - Li Hong Wang; Na Jiang; Bo Zhao; Xiao Dong Li; Tian Hong Lu; Xiao Lan Ding; Xiao Hua Huang (JBIC Journal of Biological Inorganic Chemistry, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Effects of sevoflurane preconditioning and postconditioning on rat myocardial stunning in ischemic reperfusion injury - An-lu Dai; Li-hua Fan; Feng-jiang Zhang; Mei-juan Yang; Jing Yu; Jun-kuan Wang; Tao Fang; Gang Chen; Li-na Yu; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Species and distribution of rare earth elements in the Baotou section of the Yellow River in China - Jiang He; Chang-Wei Lü; Hong-Xi Xue; Ying Liang; Saruli Bai; Ying Sun; Li-Li Shen; Na Mi; Qing-Yun Fan (Environmental Geochemistry and Health, 2010)

Identifying wetland change in China’s Sanjiang Plain using remote sensing - Shuqing Zhang; Xiaodong Na; Bo Kong; Zongming Wang; Hongxing Jiang; Huan Yu; Zhichun Zhao; Xiaofeng Li; Chunyue Liu; Patricia Dale (Wetlands, 2009)

Molecular cloning, characterization and expression of two rapeseed (Brassica napus L.) cDNAs orthologous to Arabidopsis thaliana phenylalanine ammonia-lyase 1 - Yu Ni; Hong-Lin Jiang; Bo Lei; Jia-Na Li; You-Rong Chai (Euphytica, 2008)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Construction and characterization of a transformation-competent artificial chromosome (TAC) library ofZizania latifolia (Griseb.) - Fan Na Kong; Shao Mei Jiang; Li Xue Shi; Cheng Li Song; Min De Jin; Shao Lin Jiang; Manli Weng; Bin Wang (Plant Molecular Biology Reporter, 2006)

Polymorphism and chromosomal mapping of the mouse gene for B-cell activating factor belonging to the tumor necrosis factor family (Baff) and association with the autoimmune phenotype - Yi Jiang; Mareki Ohtsuji; Masaaki Abe; Na Li; Yan Xiu; Xiang Wen; Toshikazu Shirai; Sachiko Hirose (Immunogenetics, 2001)